1999
DOI: 10.1002/j.2333-8504.1999.tb01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Global Self‐ratings of Esl Speaking Proficiency Based on an Fsi/Ilr‐referenced Scale

Abstract: This study explored the validity and potential utility for self-assessment of speaking proficiency in English as a second language (ESL), of a self-rating scale intended to nominally parallel--in terms of number of points or levels and corresponding descriptions oflanguage-use behavior--a scale used by members of the Interagency Language Roundtable (ILR) to rate performance in Language Proficiency Interviews (LPI). The study sample was composed primarily of educated, adult ESL users/learners, most of whom were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…Previous findings suggest that specific self-assessments correlate more highly with test scores in various domains (e.g., Ackerman et al, 2002;Mabe and West, 1982) including language (Brantmeier and Vanderplank, 2008;Brantmeier et al, 2012;Ross, 1998). Although our performance SA measure differs in several respects from the specific measures that show particularly high correlations in other studies (these instruments, for instance, often refer to real-life situations rather than study tasks and typically have a larger number of items or describe the criteria in great detail; see LeBlanc and Painchaud, 1985;Wilson, 1999), it is clearly more specific than general ability SAs. Therefore, we expected performance SAs to correlate more closely with test scores and to show a higher congruence with regression models using test scores compared with ability SAs.…”
Section: Two Types Of Self-assessmentmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous findings suggest that specific self-assessments correlate more highly with test scores in various domains (e.g., Ackerman et al, 2002;Mabe and West, 1982) including language (Brantmeier and Vanderplank, 2008;Brantmeier et al, 2012;Ross, 1998). Although our performance SA measure differs in several respects from the specific measures that show particularly high correlations in other studies (these instruments, for instance, often refer to real-life situations rather than study tasks and typically have a larger number of items or describe the criteria in great detail; see LeBlanc and Painchaud, 1985;Wilson, 1999), it is clearly more specific than general ability SAs. Therefore, we expected performance SAs to correlate more closely with test scores and to show a higher congruence with regression models using test scores compared with ability SAs.…”
Section: Two Types Of Self-assessmentmentioning
confidence: 91%
“…They found correlations up to .80 between the self-assessments and test scores. A study of adult learners of English as a foreign language that used self-assessments describing levels of speaking and listening ability in great detail reported similarly high correlations with participants' test performance (Wilson, 1999).…”
Section: Correlations Between Self-assessed and Tested Language Profimentioning
confidence: 93%
See 2 more Smart Citations
“…Research over the years has shown that self-ratings for language competence tend to be accurate and correlate moderately to highly with competence scores on standardized tests, as concluded by LeBlanc & Painchaud (1985) , Blanche and Merino (1989), and Ross (1998) from their extensive review of earlier research on self-assessment. Later studies lent further support to the value of self-assessment (e.g., Oscarson, 1997;Wilson & Lindsey, 1999;Yoshizawa, 2009).…”
Section: Methodsmentioning
confidence: 91%